2013
DOI: 10.1007/s00192-013-2090-2
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen years’ follow-up of the tension-free vaginal tape procedure for female stress urinary incontinence

Abstract: The TVT operation is durable for 17 years, with a high satisfaction rate and no serious long-term tape-induced adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
149
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 21 publications
12
149
0
6
Order By: Relevance
“…(10) Most studies report a cure rate of 90% with TVT and TVT-O. (14)(15)(16) In our study, a postoperative subjective cure rate of 90.8% and objective cure rate of 86.8% (data not presented) was observed at six months. The remaining patients had signifi cant improvement of their symptoms.…”
Section: Discussionmentioning
confidence: 46%
“…(10) Most studies report a cure rate of 90% with TVT and TVT-O. (14)(15)(16) In our study, a postoperative subjective cure rate of 90.8% and objective cure rate of 86.8% (data not presented) was observed at six months. The remaining patients had signifi cant improvement of their symptoms.…”
Section: Discussionmentioning
confidence: 46%
“…There were no late adverse effects. In a study by Nilsson et al [22] looking at 17-year follow-up, they report that 48 of 55 (87.2%) of the women regarded themselves cured or significantly better than before surgery. Objective cure, defined as a negative stress test, was seen in 42 of 46 women (91.3%).…”
Section: Retropubic Midurethral Slingsmentioning
confidence: 99%
“…Over 20 years ago it was suggested that mid-urethra played a pivotal role in achieving urinary continence. Suburethral retropubic tape TVT was then introduced and showed a high treatment efficacy with long lasting effects [5][6][7][8][9][10][11]. Introital pelvic floor sonography performed with a transvaginal probe (PFS-TV) showed to be useful in evaluating the implanted suburethral tapes.…”
Section: Introductionmentioning
confidence: 99%